Numerical and experimental investigation on performance of convex-cut baffles in shell-and tube heat exchanger (2020)
In this study, comparative performance of single-segmental baffle and a newly developed baffle –convex-cut in shell-and-tube heat exchanger were both numerically and experimentally investigated. For the numerical analysis, three working fluids (engine oil, water and air) were successively utilised on the shell-side of heat exchangers with 30, 35, 40 and 45% convex-cut (CeC_STHE) and 25% segmental (SS_STHE) baffles, and the resulting models were solved in COMSOL Multiphysics. Experiments were carried out on 30% CeC_STHE and SS_STHE exclusively running on water. The data obtained were used to determine the weighted shell-side heat transfer coefficient and weighted performance factor of each heat exchanger. Hence, the results for all the ranges of Reynolds number indicate that the shell-side heat transfer coefficients of all the CeC_STHEs are lower than that of SS_STHE except for the 30% CeC_STHE. However, the SS_STHE showed greater pressure drop than the CeC_STHEs. The choice of working fluid had more influenced on the weighted shell-side heat transfer coefficient CeC_STHE. Moreover, the weighted performance factors of the CeC_STHEs indicated positive values. Thus, 30% CeC_STHE demonstrated a better performance while the 45% had the lowest performance.